Intervensi Untuk Meningkatkan Kemampuan Kognitif Pada Anak Tunadaksa: A Scoping Review - Elfira Rosa Karnaini; Latifah Rahmi. R; Shafiyya Rahma Khoerunnisa; Nailun Najah; Iftita Rahmi (CV. ITTC INDONESIA, 2026)
Cognitive ability is one aspect often hampered in children with physical disabilities, particularly those with cerebral palsy, requiring interventions to support their development. This article aims to map various cognitive interventions used to improve cognitive abilities in children with physical disabilities. The method used was a scoping review referring to the PRISMA-ScR guidelines. Articles were searched through the PubMed, ScienceDirect, and Google Scholar databases, covering publications from 2020 to 2025. Based on a selection process based on inclusion and exclusion criteria, nine articles were selected for analysis. The study results indicate that the interventions used include computer-based cognitive training, the Cognitive Orientation to Daily Occupational Performance (CO-OP) approach, interventions integrating neurological, motor, and cognitive aspects, and game-based approaches and dual-task activities. These interventions contribute to improvements in executive function, memory, attention, social cognition, daily activity skills, and functional status. These findings suggest that developing cognitive abilities in children with physical disabilities can be achieved through various approaches involving cognitive, motor, and metacognitive aspects.